2009
DOI: 10.1039/b822862k
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical actuation of macroscopic carbon nanotube structures: mats and aligned ribbons

Abstract: The electromechanical actuation of macroscopic carbon nanotube (CNT) structures, including single and multi walled CNT mats and aligned ribbons, is analyzed and compared. From experimental evidence, actuation due to quantum chemical and electrostatic effects can be distinguished. Their respective contribution to the total actuation depends on two key parameters, namely Young's modulus and charge density. While mechanical energy densities of actuated structures are appreciable, electromechanical conversion effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…However, a strong inverse correlation of Young's modulus and free strain is reported. 10 Fig. 1 represents similar results with respect of mechanical properties linked to different manufacturing strategies.…”
Section: Introductionsupporting
confidence: 78%
“…However, a strong inverse correlation of Young's modulus and free strain is reported. 10 Fig. 1 represents similar results with respect of mechanical properties linked to different manufacturing strategies.…”
Section: Introductionsupporting
confidence: 78%
“…Just a few examples of proposed graphene applications include nano-electronics, 2 biosensing, 3 solar energy harvesting, 4 desalination, 5 and actuation. [6][7][8][9]12,13 In a recent article, we investigated the electromechanical response of pristine monolayer graphene both in air and upon immersion in a liquid electrolyte, 12 where it was shown that the presence of an electrostatic double-layer (EDL) is necessary to produce high strain generation in pristine graphene and carbon nanotube (CNT) based actuators. However, an inherent limitation associated with actuation via the EDL effect is the low actuation rates.…”
mentioning
confidence: 99%
“…Both explanations might hold as well for the MWCNT/PPy hybrids. Additionally, the adhesion to the MWCNTs, which have a relatively high stiffness and negligible actuation strain, strongly restricts the expansion/contraction in direction parallel to the MWCNT orientation and therefore increases the relative differences of the actuation strains for the parallel (in‐plane) and perpendicular (out‐of‐plane) direction (thin polypyrrole film: out‐of‐plane/in‐plane: 18%, MWCNT/PPy perpendicular/parallel: 143%). The actuation force is transferred throughout the film thickness, perpendicular to the global MWCNT orientation by the contact points that are established during coating of the MWCNTs.…”
Section: Resultsmentioning
confidence: 99%